Evaluasi Pelaksanaan Clinical Skills Laboratory berbasis Pembelajaran Jarak Jauh Fakultas Kedokteran Gigi Universitas YARSI - Hatta, Ridhayani; Ardinansyah, Agus (Majalah Sainstekes, 2024)
Background: During the COVID-19 pandemic, all Faculty of Dentistry in Indonesia conducted online theoretical learning. However, the clinical skills learning could not be implemented because it is hampered by limited facilities and infrastructure. Faculty of Dentistry, Universitas YARSI tries to develop a method of implementing a distance learning-based skills laboratory so that the activities can still be carried out. Objective: This study aimed to evaluate the implementation of a distance learning-based clinical skills laboratory (CSL), Faculty of Dentistry, Universitas YARSI. Methods: The research was conducted with a descriptive observational and cross-sectional study design on all undergraduate students of the Faculty of Dentistry, Universitas YARSI who took part in distance learning-based CSL, by filling out a modified questionnaire. Results: The preparation, implementation, lecturers, and instructors of the distance learning-based CSL have been carried out well and are an alternative to face-to-face learning, students also did not experience significant obstacles in their learning process. Conclusion: The implementation of distance learning-based CSL, Faculty of Dentistry, Universitas YARSI can be an option for skills lab that cannot be done face-to-face, by maximizing all methods used, learning objectives can still be achieved.